The difficult reception of Durkheim at the National University of Litoral (1910-1947) (Quinto Sol, 2021)
The present work aims to study the reception of Emile Durkheim´s ideas in the “Sociology” chair of the School of Law of the University of Litoral between 1910-1947. To achieve it, the text focus on the books, articles, class notes, etc., of those who were professors of the afore chair: Gustavo Martínez Zuviría, José Oliva, José María Rosa and Francisco Ayala. Throughout the text, a difficult diffusion of French sociology among the first Santa Fe professors will be appreciated, which did not, however, prevent the apparition of original readings and applications of the theory of the Alsatian intellectual.
Keywords: Durkheim; reception; university; sociology